A novel POU family transcription factor is closely related to Brn-3 but has a distinct expression pattern in neuronal cells. - Lillycrop, K A (1992)
The use of the polymerase chain reaction in conjunction with degenerate oligonucleotides has allowed the isolation of cDNA clones derived from each of the POU family transcription factors expressed in the proliferating ND7 neuronal cell line. In addition to the previously characterized Oct-1, Oct-2 and Brn-3 factors, ND7 cells have been shown by this means to express a novel POU factor. This factor is closely related to Brn-3 but differs at seven amino acids in the POU domain, one of which is located in a region which is critical for protein-protein interactions between different POU proteins. Like Brn-3, the novel factor is expressed at high levels in embryonic brain and declines in abundance during neuronal development. In contrast to Brn-3 however, it is absent in mature sensory neurons and its expression declines during the in vitro differentiation of ND7 cells to a non-dividing phenotype whilst Brn-3 expression increases. The significance of these distinct but overlapping expression patterns is discussed in terms of the possible role of these two factors in regulating neuronal gene expression.